2017
DOI: 10.1177/1098612x17692470
|View full text |Cite
|
Sign up to set email alerts
|

Management of feline tibial diaphyseal fractures using orthogonal plates performed via minimally invasive plate osteosynthesis

Abstract: Objectives The objective was to assess the medium- and long-term outcomes (radiographic and owner questionnaire) of feline tibial diaphyseal fractures with orthogonal plate fixation via a minimally invasive plate osteosynthesis (MIPO) approach. Methods Medical records and radiographs of cats that had tibial diaphyseal fractures stabilised with orthogonal plates were obtained (2012-2016). Immediate postoperative radiographs were reviewed to assess the construct configuration and follow-up radiographs (where ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 54 publications
0
32
1
1
Order By: Relevance
“…17,37,38 If CCP are to be used in tibial fractures that are unable to be reconstructed, supplemental fixation in the form of an intramedullary pin or orthogonal plate may be advisable. 39,40 Further clinical investigation of both plating systems is warranted to determine optimal applications when stabilizing tibial fractures in cats.…”
Section: Discussionmentioning
confidence: 99%
“…17,37,38 If CCP are to be used in tibial fractures that are unable to be reconstructed, supplemental fixation in the form of an intramedullary pin or orthogonal plate may be advisable. 39,40 Further clinical investigation of both plating systems is warranted to determine optimal applications when stabilizing tibial fractures in cats.…”
Section: Discussionmentioning
confidence: 99%
“…And in present study, there were no significant intra-or postoperative complications with either procedure. According to reports from human medicine, postoperative complications with MIPO occur rarely and include superficial or deep infection, screw loosening or breakage, implant failure, delayed union, nonunion, and mal-aligned union (Hasenboehler et al, 2007;Ronga et al, 2010;Buckley et al, 2011;Craig et al, 2018;Townsend and Lewis, 2018). Several studies have reported the rate of delayed union or non-union to be 5-17% (Hasenboehler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it applies a bone plate as a bridge fashion without surgically approaching the fracture site (Peirone et al, 2012). Recently, the use of MIPO has been reported for the treatment of radius and tibia fractures in small dogs and cats to reduce iatrogenic vascular destruction (Hudson et al, 2012;Pozzi et al, 2013;Craig et al, 2018). The purpose of this study was thus to compare the clinical and functional outcomes through radiographic evaluation, visual lameness scoring, weight bearing time and range of motion between ORIF and MIPO in radial fracture gap models.…”
Section: Introductionmentioning
confidence: 99%
“…The authors are not aware of any study focusing on the benefits/limitations of an OBDNT approach compared with other methods. Numerous MIO techniques are reported in the veterinary literature for the treatment of long bone fractures, including external skeletal fixation, minimally invasive plate osteosynthesis (MIPO), and interlocking nails . Minimally invasive osteosynthesis techniques have also been applied to articular fractures, sacroiliac joint luxation stabilization, and central tarsal bone luxation stabilization .…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive osteosynthesis techniques have also been applied to articular fractures, sacroiliac joint luxation stabilization, and central tarsal bone luxation stabilization . Reported advantages of MIO/MIPO techniques in human and veterinary patients include reduced postoperative pain, preservation of the fracture hematoma, improved vascularization of the fracture site, more rapid healing, fewer wound complications, and faster return to normal function compared with open approaches . Disadvantages reported include the technical difficulty of the learning process, longer operating times, prolonged healing, fracture malreduction, and radiation safety issues associated with intraoperative fluoroscopy .…”
Section: Introductionmentioning
confidence: 99%